Areca nut and betel quid without tobacco are neither harmful nor carcinogenic: scientific evidences - Bhat S., Keshava; S., Mythri; Bhat, Sukesh (International Journal of Research in Medical Sciences, 2026)
Arecanut, the seed of Areca catechu palm, is the most popular chewing substance in most parts of the world. This nut is also called as betel nut in several countries as it is invariably chewed along with the leaf of betel (Piper betle) vine and lime (calcium hydroxide). This chewing mixture is popularly called betel quid. Lots of scientific papers and reports highlight arecanut chewing as carcinogenic to humans. If such observations are really true, the results should be repeatable and consistent in other identical studies. Strangely, several researchers could not arrive at that conclusion in similar studies. Such research papers are retrieved and presented in this review. While going through several reports which highlighted arecanut chewing as dangerous or carcinogenic, it was observed that in most of such papers the conclusions were drawn hastily and lots of lacunae observed in the methodology. Most important one is that in several such studies, data were collected on mixtures of chewing substances such as betel quid, pan masala, gutkha, etc but the authors wrongly titled the paper as arecanut or betel nut chewing as if all such chewing mixtures contain only arecanut. Contamination and adulteration of arecanut, the dosage of arecanut extract used in such experiments were some of the other factors for this ambiguity. These findings underscore the need for specific interventions to address the issue more scientifically.